Community Participation in NGO Funded Classroom Construction and Water Supply Projects in Kibaha District, Tanzania - Malipula, Mrisho M; Ezekiel, Mangi J. (UI Scholars Hub, 2023)
Community participation in development projects has been sustained rhetoric despite the rise of NGOs, which are regarded as efficient in affording participatory development practices. This article examines the nature and level of community participation in classroom construction and water supply projects implemented in partnership with NGOs in Tanzania. It examines community participation at different stages of the project cycle, the costs and benefits of motivational effect on community members' participation, the contribution of the sense of ownership and sustenance on community participation, as well as how community participation in development projects can be enhanced. Face-to-face interviews with 122 participants and documentary reviews meant to triangulate the information garnered from the interviews were used to address the questions that the study assigned itself to. The study confirmed the incongruity between the betwixt theory and practice of community development in NGO-funded development projects, depicting nagging expert-driven elements in NGO endeavors. The level of community participation is low (mainly evident in the implementation stage) and is informed by lucid calculation of the costs and benefits of a project, the sense of community ownership and sustenance, as well as the presence of a platform for community members to engage. As such, it is recommended that NGOs and other development agencies incorporate the needs of different categories of people from the start to the end of the project cycle, empower community members to participate, and provide genuine platforms for them to do so.